A Critique on Growth Studies and Analysis on the Shock Resistance of Iran’s Growth Rate in the Context of Resistance Economy - Seyyed Shamseddin Hosseini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
As oil sector has a great share in the Iran’s economic growth rate, the concept of economic growth shock resistance and stability has gained great momentum. The aim of this paper is to identify the shock resistance of Iran’s economic growth from 1978 to 2016 with the approach of “quality-sectoral analysis” in the framework of growth sectoral accounting. Results show that the economic growth rate during this period has varied about 46 percent in which oil sector growth rate has a variation of 195.4 percent. It is also verified that the largest growth shocks happened in years of oil sector production quantity shocks due to an exogenous reason like oil purchase sanctions. Two years of 1981 and 2012 are eminent in this issue. On the other hand, on the event of sanctions lift or suspension in 1983 and 2016, the growth rate experienced a jump which cannot be considered as standing in the line of long run and stable growth rate, but a short-term reform happened in the growth rate. Results of the paper show that the shock of oil sector has made the economic growth unstable due to its high dependency to foreign countries as a result of governmental supply monopoly, demand monopoly and the U.S. sanctions on Iran oil exports.